Lifeboat Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Constance 'Connie' Porter (Tallulah Bankhead) on the lifeboat before the others get into it. Bankhead came out of a 10 year retirement to do this movie. RESTRICTED USE. Digital copy only. No hard copy.